Effect of Training on Small-Scale Rice Production in Northern Ghana - Anang, Benjamin Tetteh; Awuni, Joseph A. (Applied Studies in Agribusiness and Commerce, 2018)
Training in modern farming methods enables farm households in developing countries to improve agricultural productivity. Notwithstanding the efforts of governmental and non-governmental organisations to provide farmers with agricultural training, productivity remains low. The existing literature provides little empirical evidence of the effect of training on agricultural productivity in Ghana. This study therefore seeks to bridge this gap by investigating small scale rice farmers’ participation in agricultural training programmes and its effect on productivity in northern Ghana. A treatment effect model was used to account for sample selection bias. The results indicated that participation in training increased with the number of extension visits, group membership, access to credit and the degree of specialisation in rice production. Furthermore, total output and labour productivity both increased with participation in training but the relationship with land productivity (yield) was insignificant. On average, participation in training was associated with 797kg increase in rice output, while labour productivity increased by 7.3kg/man-day. With the exception of farm capital, all the production inputs had a positively significant relationship with output suggesting sub-optimal use of capital in production. The study concludes that farmers’ training needs are not adequately being met while inadequate capital is constraining farm output. Increasing access to extension service and involving farmer-based organisations in the design and implementation of training programmes will enhance participation and farm performance. JEL Classification: C21, D24, Q12